2022
DOI: 10.1155/2022/1193734
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NADPH Oxidase Pathway Reduces Ferroptosis during Septic Renal Injury in Diabetic Mice

Abstract: Background. Obesity and type 2 diabetes mellitus (DM) contribute to a higher mortality rate in patients with septic acute kidney injury (AKI) during sepsis. Reactive oxygen species (ROS) is the major injury factor for sepsis. This study was aimed at exploring the potential therapeutic drug for septic AKI targeting on ROS. Methods. A murine septic AKI model was established in both wild-type and high-fat diet-fed (HFD) mice. NADPH oxidase inhibitor Vas2870 was used in vivo to explore the role of NADPH oxidase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Fang et al [ 36 ] showed that ferroptosis could enhance autophagy by inhibiting PI3K, downregulate the expression of beclin-1, upregulate the expression of p62, and reduce the ratio of LC3 II/LC3 I, thus reducing the inflammatory response of macrophages induced by LPS. After neuronal apoptosis, ferroptosis treatment can significantly downregulate the mRNA and protein expression levels of beclin-1 and LC3 II/lc3 I, inhibit autophagy, and play an organ protective role [ 37 ]. Under normal circumstances, the autophagy level of the body is low.…”
Section: Effect Of Ferroptosis On Anti-inflammatory Activity Of Macro...mentioning
confidence: 99%
“…Fang et al [ 36 ] showed that ferroptosis could enhance autophagy by inhibiting PI3K, downregulate the expression of beclin-1, upregulate the expression of p62, and reduce the ratio of LC3 II/LC3 I, thus reducing the inflammatory response of macrophages induced by LPS. After neuronal apoptosis, ferroptosis treatment can significantly downregulate the mRNA and protein expression levels of beclin-1 and LC3 II/lc3 I, inhibit autophagy, and play an organ protective role [ 37 ]. Under normal circumstances, the autophagy level of the body is low.…”
Section: Effect Of Ferroptosis On Anti-inflammatory Activity Of Macro...mentioning
confidence: 99%
“…The early phase of HTGP is generally believed to be an unregulated inflammatory response or a cytokine storm that results in organ damage and death[ 31 , 32 ]. Pro-inflammatory cytokines, such as TNF-α, IL-6, and IL-1ÎČ, are considered pivotal mediators for initiating, amplifying, and perpetuating organ injury[ 33 - 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that Fer‐1 and DFO can effectively support bone regeneration through increasing the abundance of type H vessels and osteoprogenitors. Moreover, Fer‐1 and DFO have proven effective to treat obesity‐related liver and kidney diseases 38,84–86 . Therefore, Fer‐1 and DFO are potential drugs for the treatment of obesity‐related osteoporosis.…”
Section: Discussionmentioning
confidence: 99%